Titanium disilicide formation by wide-area electron beam irradiation - Geller, J. D., author; Russell, P. E., author; Collins, G. J., author; Rocca, Jorge J., author; Moore, Cameron A., author; American Institute of Physics, publisher (Colorado State University. Libraries, 1984)
We describe the use of a wide-area (38 cm2) electron beam as a heat source to interdiffuse 400-Å-thick sputter-deposited titanium films into 3-6-Ω cm(100) n-type silicon wafers. Isochronal exposures of 30 s with electron beam of current densities greater than 250 mA/cm2 reduced the as-deposited sheet resistance by a factor of 10, while exposures at half this current caused the sheet resistance to increase by a factor of 2.5. Compositional depth profiles obtained from a combination of ion beam sputtering and Auger electron spectroscopy show that this resistivity increase is caused by diffusion of oxygen into the titanium film induced by the electron beam heating. At exposures to beam intensities sufficient to induce complete silicide formation, oxygen is segregated at the surface by the advancing silicon. We conclude that the silicide self-cleanses itself of oxygen during formation.